Behavioral Assumptions of Islamic Economics Revisited Is the Giving Behavior of Muslims Different from Others? - Murat Çokgezen; Mohammed Seid Hussen (Türkiye İslam İktisadı Dergisi)
Islamic economics (IE) assumes an altruistic economic agent who spends his income not only on himself but also on others through charity. Since this behavioral norm is attributed only to Muslims, this implies that the giving behavior of Muslims is different from others. This study aims to test the validity of this assumption by analyzing a cross-national survey measuring the attitudes, beliefs and behavior patterns of diverse populations in 19 European countries. The empirical results based on a logistic regression and Propensity Score Matching approach indicate no difference between Muslims and members of other religions in terms of the likelihood of involvement in giving activities. The impact of other explanatory variables on both donations and volunteer efforts were generally the same, with the exception of age and marital status. The increasing number of studies supporting the findings of this study or raising questions about the validity of Islamic economic assumptions may cause IE to reformulate its theory.